PERENCANAAN ANGGARAN BELANJA PADA BADAN PERENCANAAN PEMBANGUNAN, PENELITIAN DAN PENGEMBANGAN (BAPPELITBANG) KOTA BANDUNG TAHUN 2019-2020 - Rika Diyah Ramadhani; Wawan Setiawan Abdillah; Ai Siti Farida (Publik: Jurnal Manajemen Sumber Daya Manusia, Administrasi dan Pelayanan Publik, 2022)
Budget planning is the initial stage for the running of government activities. Budget planning becomes an instrument or tool in evaluating and monitoring government performance to achieve the intended mission vision. This research aims to find out the budget planning in Bappelitbang Bandung city in 2019-2020 reviewed from the principle of preparing APBD. This research uses qualitative methods with a descriptive approach. Data collection techniques use observation, interviews, documentation and triangulation. The determination of informants in this study was done with purposive sampling techniques. In processing and analysis of data is carried out with three series including data reduction, presentation of data, and verification or drawing conclusions. The results showed that the budget planning in Bappelitbang Bandung city in 2019-2020 was reviewed from the principle of preparing APBD has been going well. However, there are several obstacles in budget planning, including due to the covid 19 pandemic that causes less than maximum budget uptake and lack of human resources in terms of budget planning.